KEPEMIMPINAN TRANSFORMASIONAL, KEPEMIMPINAN TRANSAKSIONAL DAN BUDAYA ORGANISASI - Hestika, Wenny (Jurnal Ilmu Administrasi Negara, 2017)
Abstract: Transformational Leadership, Transactional Leadership and Organizational Culture. The purpose of this study to determine and analyze the effect of transformational leadership and transactional leadership on organizational culture in rural credit banks Local Company Rokan Hulu. This study uses a quantitative approach with a population of 35 respondents. The technique of collecting data through questionnaires and observation. Analysis of data using multiple linear regression. Contribution of the independent variable (X) on the dependent variable (Y) that is equal to 54.9%. This shows that transformational leadership and transactional leadership affect the Company’s organizational culture Regional Rural Banks Rokan Hulu.